The Framework for Resilient Industry A Holistic Approach for Developing Economies - Kumar, Narinder (Emerald Publishing Limited, 2024)
The Framework for Resilient Industryexamines the historical background, current status, and future opportunities and challenges of the Indian industry, delving into region-specific issues such as micro, small, and medium enterprises (MSMEs), economic policy, risk management and sustainable industries
Description based on publisher supplied metadata and other sources
Keywords: Economics